2011
DOI: 10.1519/jsc.0b013e3181d6848e
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Graduated Compression Stockings on Running Performance

Abstract: The aim of this study was to examine the effects of wearing different grades of graduated compression stockings (GCS) on 10-km running performance. After an initial familiarization run, 9 male and 3 female competitive runners (VO₂max 68.7 ± 5.8 ml·kg⁻¹·min⁻¹) completed 4 10-km time trials on an outdoor 400-m track wearing either control (0 mm Hg; Con), low (12-15 mm Hg; Low), medium (18-21 mm Hg; Med), or high (23-32 mm Hg; Hi) GCS in a randomized counterbalanced order. Leg power was assessed pre and postrun v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
78
3
6

Year Published

2016
2016
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(112 citation statements)
references
References 14 publications
12
78
3
6
Order By: Relevance
“…• No differences in the physiological variables of heart rate, oxygen consumption, rating of perceived exertion, or lactate levels were found with the use of GCS. [3][4][5][6] • Two studies, 1 with 2 separate experiments, showed no difference in running performance while wearing GCS. 3,6 • Two studies showed that GCS were effective in improving performance as measured by either maximal work 5 or running performance.…”
Section: Summary Of Search "Best Evidence Appraised"mentioning
confidence: 99%
See 3 more Smart Citations
“…• No differences in the physiological variables of heart rate, oxygen consumption, rating of perceived exertion, or lactate levels were found with the use of GCS. [3][4][5][6] • Two studies, 1 with 2 separate experiments, showed no difference in running performance while wearing GCS. 3,6 • Two studies showed that GCS were effective in improving performance as measured by either maximal work 5 or running performance.…”
Section: Summary Of Search "Best Evidence Appraised"mentioning
confidence: 99%
“…[3][4][5][6] • Two studies, 1 with 2 separate experiments, showed no difference in running performance while wearing GCS. 3,6 • Two studies showed that GCS were effective in improving performance as measured by either maximal work 5 or running performance. 4 • One study showed that GCS improved maximum running speed.…”
Section: Summary Of Search "Best Evidence Appraised"mentioning
confidence: 99%
See 2 more Smart Citations
“…13,17,18 Positive effects of CS, wearing on the post-exercise pain, persist for 48 to 72 h after exercise. Wearing CS also improves muscle performances during the recovery phase with positive effects on jump height 24 to 96 h after exercise.…”
Section: Clinical Studies During Recoverymentioning
confidence: 99%